Pengaruh Pemberian Virgin Coconut Oil terhadap Kadar Kreatinin dan Urea Nitrogen Darah Rattus Norvegicus Jantan - NOVIANE ANGRELLA; ROOSTANTIA INDRAWATI; LESTARI DEWI (Universitas Hang Tuah, 2020)
Abstract Background: Virgin Coconut Oil (VCO) is a functional product that is highly favored and have been widely applied in the everyday lives of society. The increase of the frequencies and duration of VCO consumption is suspected that VCO could negatively impact the target organ. The kidney is a vital organ in the human body, it is responsible for clearing out the residual waste products of metabolism in the body. The evalution of the kidney‟s function can be done through the measurement of creatinine and blood urea nitrogen. The purpose of this study is to determine the effect of VCO administration on kidney function. Method: 24 male wistar rats that are divided into 4 groups, which are listed as follows, K(-) or a negative-controlled group, P(1) or the first group of rats that are given VCO with a dose of 2mL/200gr of the rats‟ total BW/day, P(2) or the second group of rats that are given VCO with a dose of 3mL/200gr of the rats‟ total BW/day, and P(3) or the third group of rats that are given VCO with a dose of 4mL/200gr of the rats‟ total BW/day for 28 day Results: Administrating VCO with a dose of 2mL/200gr and 3mL/200gr of the rats‟ total BW/day does not affect the blood‟s creatinine level while with a dose of 4mL/200gr of the rats‟ total BW/day decreases the blood‟s creatinine level. Administrating VCO with a dose of 2 mL/200gr, 3 mL/200gr, and 4 mL/200gr of the rats‟ total BW/day does not affect the level of blood urea nitrogen. Conclusion: Administration of VCO dose of 4 mL / 200 g BW rat / day significantly decreased blood creatinine levels in experimental animals, while other doses did not affect the creatinine levels or blood urea nitrogen levels